Inhibition of lymphoproliferation and protein kinase C by synthetic peptides with sequence identity to the transmembrane and Q proteins of visna virus. - Ruegg, C L (1990)
A peptide sequence in the transmembrane protein of visna virus has been identified that bears a high degree of similarity to a sequence within the transmembrane protein gp41 of human immunodeficiency virus that we have previously shown to be immunosuppressive. Also within the Q (vif/sor) open reading frame of the visna virus genome is a sequence that is highly similar to the immunosuppressive sequence from the retroviral transmembrane protein p15E. We synthesized peptides containing these visna virus sequences and tested them for immunosuppressive activity, comparing them with their human immunodeficiency virus and leukemia retrovirus counterparts. Both the Q- and transmembrane-derived visna virus peptides inhibited lymphoproliferation stimulated by either interleukin-2 or the T-cell antigen receptor in a dose-dependent and sequence-specific manner. The two visna virus peptides also inhibited the enzymatic activity of protein kinase C, thus providing a possible molecular mechanism by which they inhibit immune function.